2023
DOI: 10.1038/s41598-023-29395-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for detecting DNA attachment on SPR biosensor

Abstract: Optoelectric biosensors measure the conformational changes of biomolecules and their molecular interactions, allowing researchers to use them in different biomedical diagnostics and analysis activities. Among different biosensors, surface plasmon resonance (SPR)-based biosensors utilize label-free and gold-based plasmonic principles with high precision and accuracy, allowing these gold-based biosensors as one of the preferred methods. The dataset generated from these biosensors are being used in different mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The research suggested that this biosensor could enhance diabetes diagnosis, particularly when used alongside standard glucose monitoring methods. 136 This study highlights the potential of this novel biosensor for practical applications, offering a rapid and inexpensive method for enhanced diabetes diagnosis.…”
Section: Biomolecular Sensingmentioning
confidence: 88%
See 2 more Smart Citations
“…The research suggested that this biosensor could enhance diabetes diagnosis, particularly when used alongside standard glucose monitoring methods. 136 This study highlights the potential of this novel biosensor for practical applications, offering a rapid and inexpensive method for enhanced diabetes diagnosis.…”
Section: Biomolecular Sensingmentioning
confidence: 88%
“…The sensor's DNA aptamer conjugation selectively binds to GA, inducing a plasmonic wavelength shift, allowing for a detection limit of 0.1 μM, which falls well within the human GA range of 20-240 μM. 136 The biosensor demonstrated its capability to provide mean glucose levels over a three-week period, correlating with the glycation status of diabetes patients. Selectivity experiments conducted with various molecules confirmed the sensor's specificity, and tests for sensor reusability yielded positive results.…”
Section: Biomolecular Sensingmentioning
confidence: 94%
See 1 more Smart Citation
“…For the proposes of DNA classification issues, frequently used techniques in the litreture are Support Vector Machines (SVM) [ 55 – 57 ], Random Forest [ 58 – 60 ], Logistic Regression [ 61 – 63 ], and K-Nearest Neighbors (KNN) [ 53 , 64 ]. The SVM algorithm creates an ideal hyperplane to divide various classes by maximizing the margin.…”
Section: Methodsmentioning
confidence: 99%
“…Surface plasmon resonance (SPR)-based optical biosensors are used because of their real-time, label-free approach, allowing high-throughput results for multi-dimensional research analysis, ranging from fundamental biological and bio-medical research to environmental and agricultural monitoring programs. [20][21][22] Commercial SPR platforms, such as BIAcore 8K and MI-S200D, are based on traditional SPR technology. The working principle is that when a beam of P-polarized light is incident on the end face of a prism within a certain angle range, the interface between the prism and the metal film will generate surface plasma waves.…”
Section: Introductionmentioning
confidence: 99%